Preparation and properties of poly(acrylamide)-grafted-kenaf fiber biodegradable hydrogel with slow release urea fertilizer - Ali Badaruddin, Ila Najaa (2014)
The purpose of this research was to study the properties of superabsorbent hydrogels based on poly(acrylamide) / biofiller and urea liquid fertelizer, by solution polymerization. Kenaf fiber (KF) was used as biofiller and the KF was grafted with poly(acrylamide) (PAAm) to produce poly(acrylamide)-grafted-kenaf fiber (PAAm-g-KF) hydrogel. Urea fertilizer was employed as a polymerization media. N, N'-methylene bisacrylamide (MBA) was used as a crosslinker and ammonium persulfate (APS) as an initiator. The grafted copolomerization of acrylamide (AAm) onto KF backbone was characterized with fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) and the effects on swelling rate, slow release, water retention and degradation rate were investigated. The application of PAAm-g-KF on plant growth was performed and observed. Results obtained showed that the maximum water absorbency of PAAm-g-KF hydrogel was achieved at 104.11 g/g when the amount of APS and MBA were 2.64 part per hundred monomer (pphm) and 0.26 pph, respectively. Meanwhile, the optimization value of KF loading was at 5.28 pphm and neutralization degree of AAm was 80%. Maximum urea release in soil was measured at 0.36 mg/ml after nine days. The addition of PAAm-g-KF greatly improved plant growth and water retention. Paam-g-KF has proven to improve the utilization of fertilizer and water resources as well as degradability of hydrogel.